Carbon emissions trading pilot policy drives enterprise new quality productivity: the mediating mechanism of green technology innovation - Li , Yan; Zhang, Xinyue (Transformations In Business & Economics, 2025)
The promotion of global green development strategies has brought significant attention to the structural contradiction between “insufficient quality and efficiency” and “virtually high quantity” of green technology innovation, particularly concerning its role in fostering new quality productivity cultivation of enterprises. However, empirical research specifically examining the influence of a carbon emissions trading pilot policy on enterprise new quality productivity, from the dual perspective of green technology innovation, remains limited. To explore the path to promote enterprise new quality productivity, drawing upon dual theory and using the data of Chinese A-share listed companies during 2012-2023, the internal action mechanism among the carbon emissions trading pilot policy, green technology innovation, and enterprise new quality productivity was analyzed through a Difference-in-Difference method. Results show that the carbon emissions trading pilot policy generates a markedly positive influence on the enterprise’s new quality productivity. In addition, the quality improvement of green technology innovation mediates this relationship. For non-state-owned, small, and high-growth enterprises, the policy exerts a stronger positive effect on new quality productivity. Furthermore, environmental attention from the government, the degree of digital transformation, and managerial performance pressure exerts positive moderating effects, whereas the degree of market competition plays a negative moderating role. These conclusions reveal the influencing mechanism of the carbon emissions trading pilot policy on enterprise new quality productivity, thereby providing a theoretical basis and practical enlightenment for economic green transformation and low-carbon, high-quality development.
Keywords: Carbon emissions trading pilot policy; quality of green technology innovation; quantity of green technology innovations; enterprise new quality productivity